LEKSIKON PERBATIKAN PEKALONGAN (Kajian Etnolinguistik) - Nur Fatehah (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
This research discusses batik lexicon in Pekalongan. The aims of this research are (1) to classify and to describe lexicon of batik-ness in Pekalongan; (2) to uncover the functions of lexicon of batik-ness in Pekalongan; and (3) to explain a reflection of cultural indication based on lexicon of batik-ness. This research uses ethnolinguistics approach as linguistic approaches, analyzing the relationship between language and culture, especially to observe how a language is used in daily routines as a means of communication of a particular society. The development in a cultural aspect (economy, social, religion, arts, science and technology, and so on) is reflected on its lexicon. Lexicon rises along with human needs to identify the existing products of culture. The lexicon of batik-ness in Pekalongan becomes the